PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PAIRED STORYTELLING BERBANTUAN WAYANG KARTUN BERGAMBAR (WAKABAR) TERHADAP KETERAMPILAN MENYIMAK DAN MOTIVASI BELAJAR SISWA - Azizah Prantijiwa, Atika; Malihatul Hawa, Anni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is driven by the low listening skills and learning motivation of students. It is observed that during listening activities, students tend to be unfocused and have difficulty understanding, which also leads to a decrease in their learning motivation. The purpose of this study is to determine the effect of the Paired Storytelling Cooperative Learning model assisted by illustrated cartoon puppets (Wakabar) on students' listening skills and learning motivation. This study uses a quantitative approach, with a quasi-experimental method and a Non-Equivalent Control Group Design. The population in this research consists of all students of SDN Tolokan. The research sample includes grade III students of SDN Tolokan, with class III B as the experimental class and class III A as the control class. Data collection techniques include tests through pretests and posttests as well as non-test techniques such as observation, structured interviews, questionnaires, and documentation. Data analysis was conducted using normality tests, Homogeneity test, independent sample t-test and simple linear regression test. The research results indicate that there is a difference in the use of the Paired Storytelling Cooperative Learning model assisted by illustrated cartoon puppets (Wakabar) on listening skills. This is evidenced by a significance value of 0.004<0.05 in the independent sample t-test, showing an average difference between the experimental class of 87.65 and the control class of 82.71. In addition, there is also a difference in the use of the Paired Storytelling Cooperative Learning model assisted by illustrated cartoon puppets (Wakabar) on students' learning motivation. This is indicated by a significance value of 0.001<0.05 in the independent sample t-test, showing an average difference between the experimental class of 60.41 and the control class of 51.29. Based on the research results, it can be concluded that the Paired Storytelling Cooperative Learning model assisted by illustrated cartoon puppets (Wakabar) can influence students' listening skills and learning motivation.